Geopolitical deadlock and phosphate shortfall behind the price hike? Evidence from Moroccan commodity markets - Marek Vochozka; Svatopluk Janek; Lenka Širáňová (Agricultural Economics (AGRICECON), 2023)
Phosphate fertilisers rank among limited conventional production aids, requiring eco-unfriendly mining methods. On the other hand, wheat is an indispensable agricultural commodity essential in the food industry. For this reason, it is appropriate to monitor the potential bivariate relationship between these commodities and to follow their future development closely. The article aims to identify a correlation (Kendall's tau) and causal (Granger causality test) between the price of Moroccan phosphate and wheat, applying vector autoregression (VAR). The results show a medium-to-strong correlation between phosphate and wheat, while causal analysis suggests a reciprocal relationship. The final prediction indicates the price stability of Moroccan phosphate and a fall in wheat prices, showing steady trends of the Moroccan phosphate and wheat market affected by the alarming situation in Ukraine. The article's drawbacks are a narrow market specialisation, which ignores other agricultural commodities. Our findings contribute to national officeholders and professional public, private and non-profit agrarian organisations. Investors may benefit from exploring turbulent exogenous variables like a critical geopolitical deadlock in Ukraine. The main contribution highlights the fact that the conventional fertiliser and wheat market situation appears to be stable and free from elements of uncertainty.